(untitled) (Research, Society and Development, 2020)
Dulce de leche is an important regional food, produced and consumed on a large scale in both Brazil and Argentina, mainly due to its characteristics, such as its easy digestion and greater nutritional value. The objective of the present work was to elaborate a goat milk sweet and analyze the sensory acceptance, preference and purchase intention of the product. Two sweet formulations were made, one standard and F1, with the addition of sweetener and pectin. The samples of dulce de leche were analyzed by 100 tasters using affective tests of hedonic scale, paired test preference and purchase intention. It can be observed that both the standard and the F1 sample of goat milk sweet light presented a good overall acceptance (average grades of 7.0 - like moderately) and purchase intention (average grades of 4.0 - would probably buy) and there was no statistically significant difference between them when assessing preference. Acceptability rates were higher than 80%, for both formulations. F1 can be considered light, as there was a 28% reduction in the carbohydrate content. Thus, the elaborated product can be classified in the category of food for special purposes, and it presented a good acceptance and feasibility for commercialization in the market.